Efficacy of access flap procedures compared to subgingival debridement in the treatment of periodontitis. A systematic review and meta‐analysis. (27th July 2020) - Sanz‐Sánchez, Ignacio; Montero, Eduardo; Citterio, Filippo; Romano, Federica; Molina, Ana; Aimetti, Mario
Abstract: Aim: This systematic review aimed to answer the following focused questions: (a) "In patients with periodontitis, how effective are access flaps (AFs) as compared to subgingival debridement in attaining probing depth (PD) reduction?" and (b) "In patients with periodontitis, does the type of AF impact PD reduction?". Material and Methods: Randomized clinical trials were searched in three databases. Besides PD, information concerning clinical attachment level (CAL) and other relevant outcomes was also collected. Meta‐analyses were performed whenever possible and results were categorized based on the initial PD. Results: Thirty‐six publications were included. AFs resulted in a significantly greater PD reduction in deep pockets (>6 mm or ≥6 mm), as compared to subgingival debridement, in short‐ ( n = 4; weighted mean difference [WMD] = 0.67 mm; 95% confidence interval [CI] 0.37, 0.97; p < .001) and long‐term studies ( n = 4; WMD = 0.39 mm; 95% CI 0.09, 0.70; p = .012), while in moderately deep pockets (4–6, 5–6 or 4–5 mm) only in short‐term studies ( n = 4; WMD = 0.34; 95% CI 0.21, 0.46; p < .001). In shallow pockets (1–3 or 1–4 mm), AFs led to greater CAL ( n = 7; WMD = −0.43 mm; 95% CI −0.56, −0.28; p < .001). There was not enough evidence to answer question PICO 2. Conclusions: AFs resulted in greater PD reduction in the treatment of deep and moderate pockets.